2017
DOI: 10.1590/1806-9061-2016-0403
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Thyme Essential Oil (Thymus Vulgaris) Added to Quail Diets on Performance, Some Blood Parameters, and the Antioxidative Metabolism of the Serum and Liver Tissues

Abstract: This study was conducted to determine the effect of diets containing different levels of thyme essential oil (TEO) on performance, some serum parameters and the antioxidative metabolism of the serum and liver tissues in quails. A total number of 200 sixteen-days-old Japanese quails (Coturnix coturnix japonica) were used in the study. The animals were divided into 4 groups; the control group was fed only basal diet but groups TEO1, TEO2 and TEO3 had thyme essential oil of 150, 300 and 450 mg/kg, respectively, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 16 publications
(23 reference statements)
9
26
0
Order By: Relevance
“…The EOs contribute in antioxidant activity because it decreased levels of MDA (the most important indicator of lipid peroxidation). Also, Gumus et al. (2017) stated that EOs significantly decreased MDA levels.…”
Section: Discussionmentioning
confidence: 99%
“…The EOs contribute in antioxidant activity because it decreased levels of MDA (the most important indicator of lipid peroxidation). Also, Gumus et al. (2017) stated that EOs significantly decreased MDA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Gumus et al [ 37 ] reported that specific polyphenols such as thymol may reduce plasma lipids by altering the hepatic triglyceride secretion, as well as inhibiting the activity of cholesterol-synthesizing enzyme 3-hydroxy-3-methylglutaryl-coenzyme A reductase. If some imbalance between the cellular free radical formation and the antioxidant defence system exists, excessive amounts of free radicals are produced, and cellular components such as the lipids are attacked.…”
Section: Discussionmentioning
confidence: 99%
“…Thyme EO significantly augmented the activity of GSH (which protects intracellular lipids against peroxidation) and SOD (which protects tissues against oxidation) and significantly decreased MDA levels (the most important indicator of lipid peroxidation; Gumus, Ercan, & Imik, ). It should be a contribution to oregano EO in antioxidant activity by additional mechanisms, because it decreased MDA levels.…”
Section: Discussionmentioning
confidence: 99%